Combined ACL and Anterolateral Ligament Reconstruction. Issue 1 (January 2018) - Saithna, Adnan; Thaunat, Mathieu; Delaloye, Jean Romain; Ouanezar, Hervé; Fayard, Jean Marie; Sonnery-Cottet, Bertrand
Abstract : Background: Clinical results of combined anterior cruciate ligament (ACL) and anterolateral ligament (ALL) reconstruction have demonstrated a significant reduction in ACL graft rupture rates and improved rates of return to sports compared with isolated ACL reconstruction1 . This finding is supported by laboratory studies that have demonstrated that combined ACL reconstruction and lateral extra-articular tenodesis procedures protect the ACL graft by load-sharing with it and by more reliably restoring normal knee kinematics compared with isolated ACL reconstruction. Description: The ACL graft is formed from a tripled semitendinosus tendon and a single strand of gracilis tendon. The femoral tunnel is drilled to provide an anatomic location intra-articularly and to exit the femur just posterior and proximal to the lateral epicondyle. The additional length of gracilis therefore exits the femoral tunnel at the anatomic origin of the ALL and is then routed (under the iliotibial band [ITB]) through a tibial tunnel, and back to the femoral origin, to reconstruct the ALL. Alternatives: Many different types of nonanatomic lateral extra-articular tenodesis procedures have been reported. The most frequently performed were the Lemaire and MacIntosh procedures; however, these, and others, were widely abandoned after poor results were reported in the 1980s. Rationale: ALL reconstruction differs from other lateral extra-articular tenodesis-type procedures because the procedure is anatomically based and can be percutaneously performed. Nonanatomic procedures (typically with a strand of ITB passed under the lateral collateral ligament [LCL]) have been reported to be associated with overconstraint, early arthritis, and an increased risk of infection2 -5 . In contrast, ALL reconstruction has been shown to restore normal knee kinematics and to avoid overconstraint when correctly fixed in full extension and neutral rotation 6 . The main concern with any type of lateral extra-articular tenodesis is based on historical reports of poor outcomes2, 3 . However, a recent study has demonstrated that combined ACL and ALL reconstruction is associated with a reoperation rate that is comparable with the rate seen after isolated ACL reconstruction, and it has a very low rate of complications7 . This makes a compelling argument for anatomic ALL and ACL reconstruction being the procedure of choice when considering an extra-articular procedure. This is further supported by the fact that, even though previous studies have demonstrated a trend toward reduced ACL graft rupture with nonanatomic lateral extra-articular tenodesis procedures, they have not shown a significant improvement in outcomes8 . Combined ACL and ALL reconstruction is currently the only type of lateral extra-articular procedure that has been demonstrated to significantly reduce the risk of ACL graft rupture and improve the rate of return to sports1 .